2006
DOI: 10.1093/jac/dkl136
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir/ritonavir exposure in treatment-naive HIV-infected children following twice or once daily administration

Abstract: Our small pilot study suggests that lopinavir/ritonavir once daily may be a suitable regimen for antiretroviral-naive children. However, due to the high interindividual variability and low concentrations in some patients, therapeutic drug monitoring may be necessary to ensure that concentrations are adequate to inhibit viral replication. A formal clinical study of lopinavir/ritonavir once daily in treatment-naive children is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
(11 reference statements)
1
20
0
2
Order By: Relevance
“…In dose-response studies (Fig. 2b), we found that the half-maximal inhibitory concentration (IC 50 ) of lopinavir was 16 Ϯ 4.2 M, which is within the range of average peak levels in sera of both adult and pediatric patients treated with lopinavir/ritonavir (31)(32)(33)(34).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In dose-response studies (Fig. 2b), we found that the half-maximal inhibitory concentration (IC 50 ) of lopinavir was 16 Ϯ 4.2 M, which is within the range of average peak levels in sera of both adult and pediatric patients treated with lopinavir/ritonavir (31)(32)(33)(34).…”
Section: Resultsmentioning
confidence: 61%
“…rum parasites but it also inhibits glucose uptake in human cells engineered such that the majority of hexose transport is through heterologously expressed PfHT. Importantly, profound reductions of glucose uptake into parasites and into PfHT-expressing human cells are achieved at lopinavir concentrations well below therapeutically achieved drug levels (31)(32)(33)(34). Of note, even lower concentrations of both lopinavir and compound 3361 are required to inhibit parasite replication than are required to inhibit glucose transport (19).…”
Section: Discussionmentioning
confidence: 99%
“…A second study was then conducted on treatment-naive children infected by HIV and showed equivalence of pharmacokinetics between the two dosing schedules. High variability and low trough concentrations (C trough ) for the QD regimen suggested that therapeutic drug monitoring (TDM) is necessary to ensure adequate concentrations (19).Lopinavir alone has a poor oral bioavailability and needs to be coadministered with subtherapeutic doses of ritonavir. The absolute bioavailability of LPV/r in humans remains unknown.…”
mentioning
confidence: 99%
“…A second study was then conducted on treatment-naive children infected by HIV and showed equivalence of pharmacokinetics between the two dosing schedules. High variability and low trough concentrations (C trough ) for the QD regimen suggested that therapeutic drug monitoring (TDM) is necessary to ensure adequate concentrations (19).…”
mentioning
confidence: 99%
“…In children and adolescents, doses as high as 467 mg/m 2 have been administered twice daily (13) and doses of 460 mg/m 2 once daily (35,40) have been administered without undue toxicity.…”
mentioning
confidence: 99%